Misteli Suomessa. Kuva tarkentuu - Issakainen Jouni; Pihlaja Kati (Luonnontieteellinen keskusmuseo Luomus, 2025)
An update is given on the recent dispersal of mistletoe (Viscum album) in the vicinity of Turku, in the southwestern part of Finland, and on the biology of the species in the country. The known main population
now comprises 1,464 bushes, in 220 locations. Deduced from the ages of the plants, these are still part of the same, first dispersal burst from an unknown ”mother colony”, probably now destroyed. Another mistletoe
population may be spreading into the outermost archipelago directly across the Gulf of Finland. In addition, unknown human actors seem to have planted mistletoes in the area since 2019. Frost sensitivity of the seedling during its first winter seems to hinder dispersal northwards.